The receptor for the subgroup A avian leukosis-sarcoma viruses binds to subgroup A but not to subgroup C envelope glycoprotein. - Gilbert, J M (1994)
The putative subgroup A avian leukosis-sarcoma virus (ALSV) receptor (Tva) was recently cloned by gene transfer (P. Bates, J. A. Young, and H. E. Varmus, Cell 74:1043-1051, 1993; J. A. T. Young, P. Bates, and H. E. Varmus, J. Virol. 67:1811-1816, 1993). Susceptibility to infection by subgroup A ALSV is conferred on cells upon transfection with cDNAs encoding tva. The hypothesis that tva encodes a specific receptor for subgroup A ALSV predicts that the Tva protein should bind to subgroup A, but not to subgroup C, envelope glycoprotein. In this study, we examined this prediction by using several biochemical assays. We established stable NIH 3T3 cell lines expressing either Tva, the subgroup A envelope glycoprotein (Env-A), or the subgroup C envelop glycoprotein (Env-C) and used them in conjunction with soluble forms of these molecules to demonstrate specific binding. When cell lysates containing Tva were mixed with lysates of either Env-A or Env-C, an immunoprecipitable complex formed between Tva and Env-A but not between Tva and Env-C. A soluble, oligomeric form, of Env-A, not Env-C, binds to cells expressing Tva. Reciprocally, a secreted form of Tva can bind to cells expressing Env-A but not to cells expressing Env-C. A specific and stable complex formed between soluble Env-A and secreted Tva as demonstrated by sucrose density gradient centrifugation. Thus, by three kinds of assays, Tva appears to bind specifically to Env-A, which is consistent with genetic evidence that it serves as the cell surface receptor of subgroup A ALSV and the main determinant of subgroup specificity.